IgG4-related disease involving the sclera. Issue 1 (January 2014) - Ohno, Kyotaro; Sato, Yasuharu; Ohshima, Koh-ichi; Takata, Katsuyoshi; Ando, Midori; Abd Al-Kader, Lamia; Iwaki, Noriko; Takeuchi, Mai; Orita, Yorihisa; Yoshino, Tadashi
Abstract A 49-year-old female patient previously treated for scleritis and uveitis-induced cataract in the right eye presented with a subretinal white lesion in the same eye. With a preliminary diagnosis of choroidal tumor, enucleation of the eyeball was performed in accordance with the patient's request. Histologic and immunohistologic examinations were consistent with immunoglobulin G4-related disease. The case demonstrates that it is important to consider IgG4-related disease in the differential diagnosis of an intraocular tumor.